A Growing Economy from a Buddhist Perspective - Tuladhar, Reena (Nepalese Journal of Economic Studies, 2025)
The modern global economy, often equates economic growth with material accumulation, but Buddhism teaches that true happiness and identity do not stem from mere materialistc possessions. Instead, it emphasizes the principle of sufficiency, meeting one’s needs without excess. Buddhist economics, as developed by contemporary scholars, prioritizes compassion over competition and promotes well-being over mere material gain. This paper aims to envision an alternative economic model rooted in Buddhist teachings, emphasizing indicators such as Gross National Happiness (GNH) and other holistic well-being indexes. Such a model would shift the focus from increasing material wealth to addressing both the physical and mental challenges facing humanity. That would also advocate for economic planning that centers ecological regeneration and non-harming principles. Original sources from the Pali Canon, along with recent research by Buddhist scholars, serve as key references for this inquiry. In an increasingly interconnected world, economy of countries is gradually integrating with global markets. As it does so, Buddhist scriptures and contemporary Buddhist economic thought offer valuable guidance for constructing a radical, values-based economic model tailored to countries unique socio-cultural context.